Mycotoxins in Seafood: Occurrence, Recent Development of Analytical Techniques and Future Challenges - Slim Smaoui; Teresa D’Amore; Sofia Agriopoulou; Amin Mousavi Khaneghah (Separations, 2023)
The co-occurrence of mycotoxigenic fungi and mycotoxins in aquatic food commodities has recently become a source of severe worldwide food insecurity since these toxicants may damage human health. The consumption of aquatic food itself represents a relatively novel and non-negligible source of mycotoxins. Mycotoxins in seafood lead to important human genotoxins, carcinogens, and immunosuppressors. Consequently, it is crucial to quantify and characterize these contaminants in aquatic food products subject to extensive consumption and develop new regulations. The present paper provides an overview of recent advancements in liquid chromatography and mass spectrometry and the coupling of these techniques for identifying and characterizing mycotoxins in various fresh, comestible, and treated marine products. The disposable data display that a multiplicity of fungal species and further mycotoxins have been detected in seafood, comprising aflatoxins, ochratoxins, fumonisins, deoxynivalenol, zearalenone, and trichothecenes. In addition, a wider and up-to-date overview of global occurrence surveys of mycotoxin occurrence in seafood in 2017–2022 is explored. In this regard, the predominant occurrence of enniatins has been documented in seafood products. Likewise, special attention has been given to current EU seafood legal and existing national regulations of mycotoxins in seafood. In this way, rigorous national and international guidelines are needed for palpable and effective measures in the future. Nevertheless, controlling mycotoxins in aquatic foods is an ambitious aim for scientists and industry stakeholders to ensure sustainable global food safety.